Effectiveness of Group Counseling with Cognitive Behavior Therapy Approach to Increase Student Career Behavior in Vocational High School Students - Dian Oktaviana; Mochamad Nursalim; Evi Winingsih (Universitas PGRI Yogyakarta, 2026)
Career behavior is a crucial factor for Vocational High School students to successfully transition into the workforce. However, many students face challenges such as low self-confidence, unclear career goals, and limited decision-making skills. This study aims to examine the effectiveness of group counseling using the Cognitive Behavior Therapy (CBT) approach in improving the career behavior of Vocational High School students. The study employed a quantitative method with a pre-test post-test control group design, involving 24 students divided into experimental and control groups. The experimental group received CBT-based group counseling across 6 sessions over three weeks, while the control group received general career guidance. Data were collected using a validated Likert-scale Career Behavior Inventory and analyzed with the Mann-Whitney U test due to the small sample size. The results showed a statistically significant difference between the two groups (U = 0.000, Z = -4.161, p < 0.05, effect size r = 0.85), with the experimental group demonstrating substantial improvements in self-awareness, self-confidence, career decision-making, and readiness for planning future careers. These findings indicate that CBT is an effective intervention for enhancing students’ career behavior. Practically, this study suggests that CBT-based counseling can be integrated into school counseling programs to better prepare vocational students for the demands of the labor market. Keywords: Career behavior, cognitive behavior therapy, vocational students, group counselling, career guidance